Evidence That Classroom-Based Behavioral Interventions Reduce Pregnancy-Related School Dropout Among Nairobi Adolescents. (April 2017) - Sarnquist, Clea; Sinclair, Jake; Omondi Mboya, Benjamin; Langat, Nickson; Paiva, Lee; Halpern-Felsher, Bonnie; Golden, Neville H.; Maldonado, Yvonne A.; Baiocchi, Michael T.
Purpose . To evaluate the effect of behavioral, empowerment-focused interventions on the incidence of pregnancy-related school dropout among girls in Nairobi's informal settlements. Method . Retrospective data on pregnancy-related school dropout from two cohorts were analyzed using a matched-pairs quasi-experimental design. The primary outcome was the change in the number of school dropouts due to pregnancy from 1 year before to 1 year after the interventions. Results . Annual incidence of school dropout due to pregnancy decreased by 46% in the intervention schools (from 3.9% at baseline to 2.1% at follow-up), whereas the comparison schools remained essentially unchanged ( p < .029). Sensitivity analysis shows that the findings are robust to small levels of unobserved bias. Conclusions . Results suggest that these behavioral interventions significantly reduced the number of school dropouts due to pregnancy. As there are limited promising studies on behavioral interventions that decrease adolescent pregnancy in low-income settings, this intervention may be an important addition to this toolkit.